The economics of ownership, access and trade in digital data - Néstor Duch-Brown; Bertin Martens; Frank Müller-Langer (European Commission, Joint Research Centre (JRC), 2017)
Despite the rapidly growing volume and economic importance of data in the digital economy, the legal framework for data ownership, access and trade remains incompletely defined in the EU and elsewhere. De facto data ownership dominates and often leads to fragmentation or anti-commons problems in data. Combined with limited access and trade, this inhibits the realisation of the full economic benefits of non-rival data. It may slow down innovation and affect the efficiency of data markets. We examine three potential sources of data market failures: externalities related to economies of scope in data, strategic behaviour of data owners and transaction costs in data exchanges. We link the legal debate on data ownership with relevant branches of the economics literature, including intellectual property rights economics, the commons and anti-commons literature, models of trade under the Arrow Information Paradox and multi-sided markets. Economists are inclined to think that well-defined private property rights are a necessary condition for an efficient resource allocation. The question in this paper is to what extent this view holds for non-rival data. We show that the allocation of data ownership or residual control rights matters, not only for private benefits but also for social welfare. The outcomes of bargaining over data ownership and access rights do not necessarily maximize social welfare. Can regulators intervene to improve these outcomes? Would a better specification of legal ownership rights or introducing access provisions to improve efficiency and reduce data market failures? There are no easy answers to these largely empirical questions. We offer no policy solutions yet and more research is required to bring economics up to speed with these questions.
Keywords: D23; K11; K12; L86; 330; digital single market; data economy; anti-commons; copyright; data trade; data ownership; property rights